Come il cervello rappresenta se stesso: alcune considerazioni - Dario Grossi (Rivista Internazionale di Filosofia e Psicologia, 2013)
How the Brain Represents Itself: Some Considerations – The approach proposed in this paper starts from the assumption that neural and mental levels must strictly correspond to each other, even though a reciprocal causal relationship between them must be excluded. Neural and mental events are considered univocal facts that can be addressed differently, depending on whether one is interested in understanding the mental or the neural level. This epistemological approach can be summarized in the following way: “everything neural corresponds to something mental, and everything mental corresponds to something neural”. Describing the principles of this correspondence is the final aim of the areas of study identified as neuropsychology and cognitive neuroscience. The insular cortex, which is situated deep within the sylvian fissure between the temporal and frontal lobes is involved, among other things, in the production of the subjective sensation of the Self, called interoception, which is used to represent the viscera and constitutes the primary basis of self-consciousness.